Uptake of polychlorinated biphenyls and organochlorine pesticides from soil and air into radishes (Raphanus sativus) - Mikes, Ondrej; Cupr, Pavel; Trapp, Stefan; Klanova, Jana (Environmental pollution (Barking, Essex, 2009)
Uptake of organochlorine pesticides and polychlorinated biphenyls from soil and air into radishes was measured at a heavily contaminated field site. The highest contaminant concentrations were found for DDT and its metabolites, and for beta-hexachlorocyclohexane. Bioconcentration factor (BCF, defined as a ratio between the contaminant concentration in the plant tissue and concentration in soil) was determined for roots, edible bulbs and shoots. Root BCF values were constant and not correlated to log K(OW). A negative correlation between BCF and log K(OW) was found for edible bulbs. Shoot BCF values were rather constant and varied between 0.01 and 0.22. Resuspended soil particles may facilitate the transport of chemicals from soil to shoots. Elevated POP concentrations found in shoots of radishes grown in the control plot support the hypothesis that the uptake from air was more significant for shoots than the one from soil. The uptake of POPs from air was within the range of theoretical values predicted from log K(OA).
Keywords: Soil Pollutants; Plant Shoots; chlorované uhlovodíky; výhonky rostlin; látky znečišťující vzduch; kořeny rostlin; Plant Roots; Environmental Monitoring; Polychlorinated Biphenyls; rezidua pesticidů; látky znečišťující půdu; polychlorované bifenyly; Hydrocarbons, Chlorinated; Pesticide Residues; Raphanus; monitorování životního prostředí; Air Pollutants